2020
DOI: 10.3390/su12155975
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Housing Provision in Informal Settlements through Land Value Capture and Inclusionary Housing

Abstract: Public-driven attempts to provide decent housing to slum residents in developing countries have either failed or achieved minimal output when compared to the growing slum population. This has been attributed mainly to shortage of public funds. However, some urban areas in these countries exhibit vibrant real estate markets that may hold the potential to bear the costs of regenerating slums. This paper sheds light on an innovative hypothesis to achieve slum regeneration by harnessing the real estate market. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the construction sector, a mechanism used in other countries is the Land Value Capture, which would allow the requisition and use of a part of any increase in the value of land for public benefit, if related to a public policy and/or investment. With this mechanism, CML would receive an agreed share of that valuation and could use it to provide capital for its programs that promote affordable housing (Nzau and Trillo 2020). Another mechanism used is inclusionary housing zoning.…”
Section: Discussionmentioning
confidence: 99%
“…In the construction sector, a mechanism used in other countries is the Land Value Capture, which would allow the requisition and use of a part of any increase in the value of land for public benefit, if related to a public policy and/or investment. With this mechanism, CML would receive an agreed share of that valuation and could use it to provide capital for its programs that promote affordable housing (Nzau and Trillo 2020). Another mechanism used is inclusionary housing zoning.…”
Section: Discussionmentioning
confidence: 99%
“…Study findings show that most significant expert solution for land acquisition challenges of the urban poor is deliberate land allocation policies that are inclusive of the urban poor. Experts submitted that government needs to deliberately reserve some parts of urban land for affordable housing provision, similar to (Nzau & Trillo, 2020) who advocated for government allocation of urban land to private developers in inclusionary housing arrangements.…”
Section: Land Acquisitionmentioning
confidence: 99%
“…Experts housing characteristics of the urban poor (Akinwande & Hui, 2022;Patel & Bartlett, 2016). These data will provide insights for suitable housing provision in consonance with (Amoako & Boamah, 2017;Average, 2019) and the prevalent mismatch between housing supply and housing demand will be mitigated (Barka & Kumar, 2020;Nzau & Trillo, 2020;Saidu & Yeom, 2020;Young, 2020). Experts concluded that housing is an ecosystem and is better treated as such.…”
Section: Land Acquisitionmentioning
confidence: 99%
“…Community empowerment in slum settlements, based on the use of renewable energy, will encourage increased effectiveness and efficiency in the use of natural resources toward sustainable urban development. That is, low-income households are faced with the challenge of meeting energy sufficiency [55].…”
Section: Conceptual Frameworkmentioning
confidence: 99%